Multi-Phase Thermal Structure & The Origin of the Broad-Line Region, Torus, and Corona in Magnetically-Dominated Accretion Disks - Philip F. Hopkins (The Open Journal of Astrophysics, 2025)
Recent simulations have demonstrated the formation of 'flux-frozen' and hyper-magnetized disks, qualitatively distinct from both classical $α$ disks and magnetically-arrested disks, as a natural consequence of fueling gas to supermassive black holes in galactic nuclei. We previously showed that the dynamical structure of said disks can be approximated by simple analytic similarity models. Here we study the thermal properties of these models over a wide range of physical scales and accretion rates. We show there are several characteristic zones: a dusty 'torus'-like region, a multi-phase neutral and then multi-phase ionized, broad line-emitting region interior to the sublimation radius, before finally a transition to a thermal accretion disk with a warm Comptonizing layer. The disks are strongly-flared with large scale heights, and reprocess and/or scatter an order-one fraction of the central disk emission. As a result, this simple accretion disk model predicts phenomena including the existence of a dusty torus and its covering factor, geometry, clumpiness, and dust temperatures; a broad-line-region (BLR) with its characteristic sizes and luminosities and ionization properties; extended scattering/reprocessing surfaces producing cooler disk continuum and apparently large observed disk sizes; and existence of warm Comptonizing layers and hard coronal gas. Remarkably, these properties emerge without our having to introduce new components or parameters: they are all part of the accretion flow if the disks are in the hyper-magnetized limit.